Dieulafoy Lesion as a Source of Bleeding: A Report of Two Clinical Cases - Goran Sarafiloski; Mimi Marinova; Pencho Tonchev (Journal of Biomedical & Clinical Research)
Dieulafoy’s lesion is a rare source of gastrointestinal bleeding. It can be found anywhere in the gastrointestinal tract, but is most commonly seen in the proximal third of the stomach. It is a submucosal artery, adjacent to the mucosal surface, with no evidence of superficial ulcers. Lesions are routinely diagnosed and treated endoscopically. Their frequency is currently not well known, because as Dieulafoy lesions can be easily missed during endoscopy, and bleeding lesions are sometimes misidentified. In this article, we describe two cases of bleeding from the upper gastrointestinal tract, manifested by hematemesis and melena. Bleeding was successfully managed endoscopically by means of injection of adrenaline solution and application of an endoscopic hemoclip.